1997
DOI: 10.1002/(sici)1097-0142(19970701)80:1<115::aid-cncr15>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Radical chemoradiotherapy for elderly patients with bladder carcinoma invading muscle

Abstract: The age of the individual must not become a strict exclusion criterion for the radical treatment of old patients with invasive bladder carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Turgeon and Souhami 20 conducted a review of the use of TMT for MIBC in elderly patients, in which they presented a table of outcomes and toxicity data from 8 publications and 4 conference abstracts, summing to a total of 496 elderly patients. [21][22][23][24][25][26][27][28][29][30][31][32] Although the definition of "elderly" is variable in the literature, Turgeon and Souhami reported the most common definition of elderly to be those aged 70 years, which was used in greater than one-half of the studies reviewed. The median reported age of patients in the reviewed studies was 78 years.…”
Section: Discussionmentioning
confidence: 99%
“…Turgeon and Souhami 20 conducted a review of the use of TMT for MIBC in elderly patients, in which they presented a table of outcomes and toxicity data from 8 publications and 4 conference abstracts, summing to a total of 496 elderly patients. [21][22][23][24][25][26][27][28][29][30][31][32] Although the definition of "elderly" is variable in the literature, Turgeon and Souhami reported the most common definition of elderly to be those aged 70 years, which was used in greater than one-half of the studies reviewed. The median reported age of patients in the reviewed studies was 78 years.…”
Section: Discussionmentioning
confidence: 99%
“…El principal factor pronóstico relacionado con el paciente es su performance status, ya que condiciona no sólo la posibilidad de tratamientos radicales (cirugía o quimioradioterapia) sino también la respuesta a los mismos. La edad, tradicionalmente considerada como de peor pronóstico, hoy no se considera un factor determinante, considerándose más importante el estado general del paciente que el que éste sea mayor 12 . Otros parámetros del paciente como el estado inmunitario, el nivel de hemoglobina, los niveles de fosfatasa alcalina sérica, se relacionan más con el performance status por lo que en la actualidad no pueden ser considerados factores pronósticos.…”
Section: Factores Relacionados Con El Pacienteunclassified
“…Through a lot of basic research, the molecular mechanism of 125 I particles in radiotherapy for malignant tumor has achieved certain results in the induction of tumor cell apoptosis and cell cycle arrest, intracellular signal transduction and inhibition of tumor angiogenesis. In patients with recurrent bladder cancer, the efficacy of the general chemotherapy regimen is limited ( 3 ). In this study, we implanted 125 I radioactive particles into the tumor, and observed the clinical efficacy of this treatment modality during recurrent bladder cancer.…”
Section: Introductionmentioning
confidence: 99%